Global Commodity and Oil Price Movements, Macroeconomic Performance and Challenges for an Emerging Economy: The Indian Experience. Issue 3 (June 2018) - Rao, D. Tripati; Goyal, Saurabh
Commodity and oil price fluctuations have significant bearing on domestic macroeconomic performance and macroeconomic policymaking of an emerging economy. The article explores the impact of non-energy commodity and oil price fluctuations on output, inflation and real exchange rate (RER) in India; and commodity and oil constituting sizeable imports. The empirical analysis carried out through vector error correction model (VECM) for the post-liberalization period 1991–2014 clearly points out that commodity and oil price shocks have a significant impact on the variation in output and prices accounting for RER adjustment and the role of a developed financial market (private credit). The RER adjusts to commodity and oil price shocks, accounting for foreign exchange reserves and financial markets (private credit). The impulse response functions indicate that one standard deviation shock in commodity and oil price persists for three to eight quarters over domestic prices and output. While these results point to lessening of commodity and oil imports through a series of medium and long-term structural-cum-policy reform measures, in the immediate, they also lend a role of intervention by monetary authority (central bank) in pursuit of inflation targeting. Conjointly, pursuance of countercyclical fiscal policy to stabilize domestic output and prices in short run are called for.